Celebrating Leslie Prusia's 45th Birthday - Watkins, Howard::::::::: (1983)
Adam Watkins, Christine Watkins, Peggy Sanders, John Olgesby, Leslie Prusia holding homemade chocolate birthday cake Frances Kamp's "Melissa" artwork on wall